2021
DOI: 10.1002/smll.202104844
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Nanozymes with Optimized Reactivity and Utilization of Active Sites for Effective Peroxidase (and Oxidase) Mimicking

Abstract: activity (2007), [1] a wide range of nanomaterials (i.e., nanozymes) has been found to exhibit this property. [2][3][4][5] However, the mechanism behind those transition metal-based mimetics is not clear until recently. [6][7][8] As illustrated in Figure 1a, the redox between their surface M n+ (oxidation) and H 2 O 2 (reduction) first generates OH radicals (step (a)), which later oxidize substrates (e.g., tetramethylbenzidine (TMB)) giving a color change for the evaluation of activity (step (b)). To complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
(135 reference statements)
1
22
0
Order By: Relevance
“…S13†). 46 In addition, our DFT results showed that the Gibbs free energy changes at the 2 HO* adsorbed on the surface of pure Pt, pure Ru, and Pt–Ru alloy were −2.731, −0.207, and −0.189 eV, respectively. Taken together, incorporating Ru atoms into the Pt lattice to form a Pt–Ru alloy could directly dissociate H 2 O 2 into 2 HO*, which indicates that the catalytic site should be ascribed to the Pt–Ru alloy as a whole rather than a single element.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…S13†). 46 In addition, our DFT results showed that the Gibbs free energy changes at the 2 HO* adsorbed on the surface of pure Pt, pure Ru, and Pt–Ru alloy were −2.731, −0.207, and −0.189 eV, respectively. Taken together, incorporating Ru atoms into the Pt lattice to form a Pt–Ru alloy could directly dissociate H 2 O 2 into 2 HO*, which indicates that the catalytic site should be ascribed to the Pt–Ru alloy as a whole rather than a single element.…”
Section: Resultsmentioning
confidence: 76%
“…4f). 46 The UV-Vis absorption spectra illustrate that the absorbance of oxTMB decreased gradually (Fig. 4g), with the absorbance at 652 nm showing a linear relationship between the absorbance and GSH concentration from 1 to 100 × 10 −6 M (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…For the latter, radicals stay on the Fe-protoporphyrin ring. Similar surface science work was also performed on single-atom nanozymes, where the OH•-mediated pathway was also identified …”
Section: Metal Oxides As a Peroxidase Nanozymementioning
confidence: 77%
“…[4] Up to date, many transition metal oxides with switchable oxidation states (e. g., V 2 O 5 , [5] Mn 3 O 4 , [6] Fe 2 O 3 , [7] Co 3 O 4 , [8] NiO, [9] Cu 2 O, [10] and CeO 2 [11][12][13][14][15] ) have been reported to exhibit this peroxidase (POD)-like activity even in their single atom form. [16][17][18][19][20][21][22] Interestingly, CeO 2 is the only reducible transition metal oxide that can mimic alkaline phosphatase (ALP) in catalyzing the hydrolysis of phosphorylated molecules [23][24][25][26][27] as that of non-reducible ZrO 2 . [28] Given that these two enzyme-like reactions undergo different catalytic mechanisms, it would be very interesting if one could precisely manipulate the reaction specificity on a pristine CeO 2 .…”
Section: Introductionmentioning
confidence: 99%